2007
DOI: 10.1007/s12078-007-9000-2
|View full text |Cite
|
Sign up to set email alerts
|

Ortho- and Retronasal Presentation of Olfactory Stimuli Modulates Odor Percepts

Abstract: Retronasal olfaction gives us information important not only for the well-being by detecting dangerous substances but also provides a basis for the pleasures of eating and drinking. However, odors presented via the retronasal route appear to evoke different sensations compared to orthonasal presentation. In this study, we differentially stimulated anterior and posterior parts of the subjects' nasal cavity with odors. Subjects were able to tell retronasal and orthonasal smelling apart; the ability of doing so s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…Orthonasal and retronasal odor pairs were rated comparably in regard to pleasantness. Previous authors found a similar relation for food odors in contrast to nonfood odors 26 . Hedonic ratings did not change as pronouncedly as intensity ratings following foam application, supporting the discussed associations.…”
Section: Discussionsupporting
confidence: 80%
“…Orthonasal and retronasal odor pairs were rated comparably in regard to pleasantness. Previous authors found a similar relation for food odors in contrast to nonfood odors 26 . Hedonic ratings did not change as pronouncedly as intensity ratings following foam application, supporting the discussed associations.…”
Section: Discussionsupporting
confidence: 80%
“…Such manipulation was not performed in the group analyses ( t test) in an effort to avoid introducing a bias in group means. Finally, individual performance on the trigeminal lateralization task was analyzed as a categorical variable (pass/fail), in which scores above 25 (out of 40) were regarded as significantly above chance level (i.e., pass) according to binomial distribution ( P < .05) . χ 2 analysis was then performed to compare pass rates between the study groups.…”
Section: Methodsmentioning
confidence: 99%
“…After each trial, subjects made a two-alternative (left/right), forced-choice judgement on the position of the stimulus by raising the corresponding hand. Task performance was assessed by counting the number of correct lateralizations (von Skramlik, 1924, von Békésy, 1964, Kobal et al, 1989, Hummel et al, 2003, Wysocki et al, 2003, Frasnelli et al, 2008) resulting in a score for each stimulus. Tests of different stimuli were separated by a 10-minute break.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting feature in humans that sets the trigeminal system apart from its olfactory counterpart is its ability to physically identify the site of stimulation (von Skramlik, 1924, Frasnelli et al, 2008). When an odorous stimulus is presented to one nostril only (monorhinal stimulation) we can only identify the stimulated nostril, if the odor also activates the trigeminal system (Kobal et al, 1989, Hummel et al, 2003, Frasnelli et al, 2009, Kleemann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%